ЖАС ӨСПИРИМЛЕРДИҢ САЛАМАТ ҲӘМ САНАЛЫ РАЎАЖЛАНЫЎЫНДА МИЛЛИЙ ОЙЫНЛАРДЫҢ ТӘСИРИ - Бердибаева, Г. (FAN va JAMIYAT, 2020)
The article is devoted to revealing the significance of the Karakalpak national children's games. The role of children's games in the development of the child's body and spirit is described by demonstrating the techniques of folk games "Arkalaspak", " Cats and Mice", "Shyr aylanba"